2013
DOI: 10.1128/jvi.01414-13
|View full text |Cite
|
Sign up to set email alerts
|

Compensatory Hemagglutinin Mutations Alter Antigenic Properties of Influenza Viruses

Abstract: c Influenza viruses routinely acquire mutations in antigenic sites on the globular head of the hemagglutinin (HA) protein. Since these antigenic sites are near the receptor binding pocket of HA, many antigenic mutations simultaneously alter the receptor binding properties of HA. We previously reported that a K165E mutation in the Sa antigenic site of A/Puerto Rico/8/34 (PR8) HA is associated with secondary neuraminidase (NA) mutations that decrease NA activity. Here, using reverse genetics, we show that the K1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 22 publications
1
29
0
Order By: Relevance
“…Antigenic changes can come at a cost of fitness, sometimes due to lower avidity to sialic acids, and substitutions outside the antigenic motif may be compensatory mutations or simply hitchhiker mutations (43,44,54,55). We selected one OH/04 mutant with large antigenic changes to assess in vivo other virus properties and found that its replication in the upper and lower respiratory tract in directly inoculated pigs was comparable to that of wt OH/04 but caused significantly lower levels of lung lesions (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Antigenic changes can come at a cost of fitness, sometimes due to lower avidity to sialic acids, and substitutions outside the antigenic motif may be compensatory mutations or simply hitchhiker mutations (43,44,54,55). We selected one OH/04 mutant with large antigenic changes to assess in vivo other virus properties and found that its replication in the upper and lower respiratory tract in directly inoculated pigs was comparable to that of wt OH/04 but caused significantly lower levels of lung lesions (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Models of pathogen evolu-tion can help to establish whether such approaches will completely stall adaptation of the pathogen or with what likelihood the designed fitness valleys would be crossed. Moreover, such approaches could also be used to explore alternative routes as a result of epistatic interactions that might allow deleterious mutations to occur if they are acquired in the right order (15,17,20).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the altered receptor-binding avidity and lower replication resulting from the antigenic escape mutation HA K165E in A/Puerto Rico/8/1934 (H1N1) could be compensated for by mutations in HA or the neuraminidase (NA) (15,16), and stabilizing mutations were required to occur prior to the introduction of immune-escape mutations in influenza A/H3N2 virus (17). Similarly, there are numerous examples where antiviral resistance-conferring mutations come at a fitness cost for the virus but can be compensated for by other mutations: several neuraminidase substitutions can occur and have occurred as either permissive or compensatory mutations to counteract the adverse fitness effects of the oseltamivir resistance mutation NA H275Y in influenza A/H1N1 virus (18)(19)(20), and similarly, the I222V NA mutation in influenza A/H3N2 virus partially restored the viral fitness-decreasing oseltamivir resistance mutation NA E119V (21).…”
mentioning
confidence: 99%
“…Why is this the case if only 1 antigenic site is antigenically important? One possible explanation is that mutations in non-immunodominant antigenic sites offset viral fitness costs associated with mutations in immunodominant antigenic sites [25,28]. An alternative explanation is that all 5 HA antigenic sites are actually antigenically relevant, but that the ferret reference sera used to create antigenic maps in these studies are not fully representative of human immunity.…”
Section: Genetic Variation Versus Antigenic Variationmentioning
confidence: 99%